A STUDY ON GENDER AND LANGUAGE DIFFERENCES IN WRITTEN TEXTS - Alkhrisheh, Hazim; Aziez, Feisal; Alkhrisheh, Taisir (Research And Innovation In Language Learning (RILL), 2019)
This study aims at investigating gender differences in written texts using Halliday’s framework about the functions of language. Halliday claimed that females’ writing style is, what he described as, ‘involved’ while males’ writing style is more ‘informative’. The results of the study do not confirm Halliday’s assumptions about gender differences in writing. No significant differences were found between males and females in the frequencies of the use of nouns, prepositions, numerals and modifiers. The only significant difference that was found is the use of pronouns, which is not enough to account for the assumptions. This paper also aims to investigate the differences between Arabic and English in the average sentence length, lexical density, and readability. To measure readability, the Gunning-Fog index formula was used. The results show that there was no significant difference between Arabic and English in the average sentence length, but there were significant differences in lexical density and readability.